EFEKTIVITAS METODE PROBLEM BASED LEARNING DALAM MENINGKATKAN KEAKTIFAN SISWA MI TARBIYATUL ATHFAL BABAT - Yulia Pramusinta (Universitas Islam Lamongan, 2019)
Student activity is one of the learning activities that should be trained to students because high scientific reasoning will affect students in making decisions and solving problems. It takes seriousness in practicing scientific reasoning skills. So the teacher must choose the appropriate learning approach. This article discusses the problem based learning model which is an inquiry-based learning model, where learning begins by giving a problem. The second discussion, introduced patterns of scientific reasoning that can be trained on students both at the concrete and formal operational stages. At the end of the discussion, the PBL model will be able to facilitate students in developing scientific reasoning